EFFECTIVENESS OF APPLE CIDER VINEGAR AS A TREATMENT OF SCABIOSIS, MALASSEZIOSIS, COMPLICATED BY OTITIS EXTERNA IN A DOMESTIC CAT - Hasby Faizul Qodri; Putu Devi Jayanti; I Gusti Made Krisna Erawan (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Apple cider vinegar is a natural substance containing acetic acid, polyphenols, vitamins, and minerals with antimicrobial, antiparasitic, and anti-inflammatory properties, making it potentially useful as a therapeutic agent for animal skin diseases. This article reports a 3-year-old domestic cat presenting with crusting, alopecia, swelling on the left anterior region of the mouth accompanied by mild hypersalivation, and the presence of moist yellow ear discharge. Supporting examinations were performed using skin scraping, native otic swab, cytological otic swab, and acetate tape preparation methods. Based on the history, clinical findings, and supporting examinations, the cat was diagnosed with scabiosis, malasseziosis, and otitis externa. The therapy administered consisted of both causative and supportive treatments. For scabiosis and malasseziosis, apple cider vinegar was used as a natural topical antimicrobial agent. The use of apple cider vinegar as a topical antimicrobial agent showed effective results in reducing the clinical signs of scabiosis and malasseziosis, characterized by improvement in skin condition and reduction of lesions within 7 days. Otitis externa was treated topically using Oridermyl® ointment administered once daily for 7 days. In addition, fish oil capsules were administered orally as supportive therapy to nourish the skin and enhance the immune system. Evaluation over a 7-day period demonstrated a reduction in crusting, alopecia, and hypersalivation, resolution of swelling in the left anterior region of the mouth, as well as decreased moist yellow ear discharge.